Pancreatic Somatostatinoma Diagnosed Preoperatively: Report of a Case - Mori, Yasuhisa; Sato, Norihiro; Taniguchi, Ryuta; Tamura, Toshihisa; Minagawa, Noritaka; Shibao, Kazunori; Higure, Aiichiro; Nakamoto, Mitsuhiro; Taguchi, Masashi; Yamaguchi, Koji (JOP. Journal of the Pancreas, 2014)
Context Somatostatinoma is a rare neoplasm of the pancreas. Preoperative diagnosis is often difficult. Case report We report a 72-year-old woman with a pancreatic head tumor measuring 37 mm in diameter, and enlargement of the lymph nodes on the anterior surface of the pancreatic head and the posterior surface of the horizontal part of the duodenum. Laboratory data showed an elevated plasma somatostatin concentration. Examination of a biopsy specimen of the pancreatic head mass obtained by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) showed histopathological features of a neuroendocrine tumor. Immunohistochemical staining showed that the tumor cells were positive for somatostatin, leading to a preoperative diagnosis of pancreatic somatostatinoma. The patient underwent pylorus-preserving pancreaticoduodenectomy. The plasma somatostatin concentration decreased progressively after surgery. Conclusions A rare case of pancreatic somatostatinoma with lymph node metastases was presented. Immunohistochemical analysis of a biopsy specimen obtained by EUS-FNA was useful for preoperative diagnosis. Image: Location of a pancreatic somatostatinoma and lymph node metastases.